2002
DOI: 10.1007/bf03345507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypothyroidism on synaptosomal-associated protein of 25 kDa and syntaxin-1 expression in adenohypophyses of rat

Abstract: The aim of this study was to analyze the expression of SNAP-25 and syntaxin-1 in the adenohypophyses of hypothyroid rats. Rats were divided into: 1) controls; 2) thyroidectomized 40 days; and 3) thyroidectomized 40 days with replacement of T4 20 days after surgery. Adenohypophyses were studied by immunohistochemistry and immunoblot analysis using antibodies against SNAP-25, syntaxin-1 and TSH. By immunostaining, SNAP-25 and syntaxin-1 were conspicuous and were localized around cytoplasmic vacuoles of thyroidec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
1
14
1
Order By: Relevance
“…Salinas et al (1999), who investigated the presence of syntaxin-1 and SNAP-25 by immunohistochemistry in different parts of the mouse, guinea pig, and cat pituitary, suggested that syntaxin-1 and SNAP-25 were involved in the hormonal secretary process of the adenohypophysis as well as the neurohypophysis of these animals. Quintanar et al (2002) analyzed the expression of SNAP-25 and syntaxin-1 in the adenohypophyses of hypothyroid rats, and found that thyroidectomy produced changes in both the expression and the immunoreactivity of SNAP-25 and syntaxin-1 in the adenohypophyses of the rats and that these effects could be reversed by T4 administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salinas et al (1999), who investigated the presence of syntaxin-1 and SNAP-25 by immunohistochemistry in different parts of the mouse, guinea pig, and cat pituitary, suggested that syntaxin-1 and SNAP-25 were involved in the hormonal secretary process of the adenohypophysis as well as the neurohypophysis of these animals. Quintanar et al (2002) analyzed the expression of SNAP-25 and syntaxin-1 in the adenohypophyses of hypothyroid rats, and found that thyroidectomy produced changes in both the expression and the immunoreactivity of SNAP-25 and syntaxin-1 in the adenohypophyses of the rats and that these effects could be reversed by T4 administration.…”
Section: Discussionmentioning
confidence: 99%
“…Since previous reports have either mainly studied rab family, or have focused exclusively on the SNARE system (Jacobsson and Meister, 1996;Lledo et al, 1993;Quintanar and Salinas, 2002;Salinas et al 1999;Tahara et al, 1999;Tasaka et al, 1998), to date these proteins have not yet been investigated together. Therefore, their mutual relationships have remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate immunoreactivity of the exocytotic membrane proteins (Syntaxin-1, Syntaxin-4, SNAP-23, and SNAP-25), the avidin-biotin peroxidase complex method (Hsu et al, 1981), using the kit (Vectastin ABC kit, Dimension Laboratories Inc., CA, USA) with slight modifications (Quintanar & Salinas, 2002). Primary antibodies raised against Syntaxin-1, Syntaxin-4, and SNAP-23 (rabbit polyclonal antiSyntaxin-1, anti-Syntaxin-4, or anti-SNAP-23, respectively.…”
Section: Immunohistochemical Methodsmentioning
confidence: 99%
“…SNAP-25 and Syntaxin-1 are located in the plasma membrane of neural, endocrine, and exocrine tissues. These proteins have been reported in glandular cells of parasitic helminthes (Quintanar & López, 2001), in frog chromaffin cells (Quintanar et al, 1998), in mast cells (Salinas et al, 2004), in the rat pituitary (Quintanar & Salinas, 2002), and in neuronal tissue of rat (Mitchell & Ryan, 2004). Nevertheless, in aquatic invertebrates there are no reports of SNAREs proteins in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Salinas et al investigated the presence of syntaxin-1 and SNAP-25 using immunohistochemical methods in different parts of mouse, guinea pig and cat pituitaries, and suggested that syntaxin-1 and SNAP-25 are involved in the hormonal secretory process of both the adenohypophysis and neurohypophysis in these species [34]. Quintanar and Salinas analyzed the expression of SNAP-25 and syntaxin-1 in the adenohypophyses of hypothyroid rats, and found that thyroidectomy resulted in changes to both expression and immunoreactivity of SNAP-25 and syntaxin-1, and that these effects could be reversed by T4 administration [32]. However, the direct function of rab3B in conjunction with the secretion of pituitary hormones and SNARE system remains unclear.…”
Section: The Snare System and Rab3b In Pituitary Cellsmentioning
confidence: 99%